Exaggerated blood pressure response to exercise and late-onset hypertension in young adults. Issue 6 (December 2017) - Yzaguirre, Ignasi; Grazioli, Gonzalo; Domenech, Mónica; Vinuesa, Antonio; Pi, Ramon; Gutierrez, Josep; Coca, Antonio; Brugada, Josep; Sitges, Marta
Abstract : Introduction: Exaggerated blood pressure response (EBPR) during exercise has been associated with an increased risk of incidental systemic hypertension and cardiovascular morbidity; however, there is no consensus definition of EBPR. We aimed to determine which marker best defines EBPR during exercise and to predict the long-term development of hypertension in individuals younger than 50 years. Patients and methods: We reviewed 107 exercise tests performed in 1992, applied several reported methods to define EBPR at moderate and maximum exercise, and contacted the patients by telephone 20 years after the test to verify hypertension status. Finally, we determined which definition best predicted incidental hypertension at 20-year follow-up. Results: The mean age of the participants at the time of exercise testing was 25.7±11.1 years. Logistic regression showed a significant association of diastolic blood pressure of more than 95 mmHg at peak exercise and systolic pressure more than 180 mmHg at moderate exercise with new-onset hypertension at 20-year follow-up [odds ratio: 6.3 (2.09–18.9) and odds ratio: 7.09 (2.31–21.7), respectively]. If EBPR was present, as defined by at least one of these parameters, the probability of incidental later onset hypertension was 70%. Conclusion: In our population, diastolic blood pressure of more than 95 mmHg at maximum exercise or systolic blood pressure more than 180 mmHg at moderate-intensity exercise (100 W) were the best predictors of new-onset hypertension at long-term follow-up. Individuals with EBPR according to these criteria should be monitored closely to detect the early development of hypertension.